Common Faults and Maintenance of Three-phase AC Asynchronous Motors - Guan Yu; Indra Yuliarta (Jurnal Indonesia Sosial Teknologi, 2024)
Application of three-phase AC asynchronous motor in industrial applied in many aspect following function that need to use. In operation use, many troubles may cause motor equipment not to operate or break down by the motor itself or caused by a system including protection, control system, interlocking device, and others causes. Aiming at the actual situation that three-phase AC asynchronous motors are widely used and have a high failure rate, this paper focuses on analyzing the common failures and abnormal phenomena of three-phase AC asynchronous motors and their main causes. This Research Method is reinforced by the actual monitoring of the locality where the equipment is installed. At the same time, some specific preventive measures and treatment methods are proposed to timely discover and eliminate the potential accidents of motors as much as possible and ensure the safe operation of motors. In conclusion, the aspects that need to be considered are one by one. There are 2 general classifications to determine possible faults, the first is about the operating conditions that the equipment motor should monitor and take the scheduled data to know about the actual conditions including power quality, temperature rise, vibration analysis, and physical abnormalities during the operation of the unit.